Pulmonary toxicity of instilled silver nanoparticles: influence of size, coating and rat strain. - Joanna Seiffert; Farhana Hussain; Coen Wiegman; Feng Li; Leo Bey; Warren Baker; Alexandra Porter; Mary P Ryan; Yan Chang; Andrew Gow; Junfeng Zhang; Jie Zhu; et al. (PLoS ONE)
Particle size and surface chemistry are potential determinants of silver nanoparticle (AgNP) respiratory toxicity that may also depend on the lung inflammatory state. We compared the effects of intratracheally-administered AgNPs (20 nm and 110 nm; polyvinylpyrrolidone (PVP) and citrate-capped; 0.1 mg/Kg) in Brown-Norway (BN) and Sprague-Dawley (SD) rats. In BN rats, there was both a neutrophilic and eosinophilic response, while in SD rats, there was a neutrophilic response at day 1, greatest for the 20 nm citrate-capped AgNPs. Eosinophilic cationic protein was increased in bronchoalveolar lavage (BAL) in BN and SD rats on day 1. BAL protein and malondialdehyde levels were increased in BN rats at 1 and 7 days, and BAL KC, CCL11 and IL-13 levels at day 1, with increased expression of CCL11 in lung tissue. Pulmonary resistance increased and compliance decreased at day 1, with persistence at day 7. The 20 nm, but not the 110 nm, AgNPs increased bronchial hyperresponsiveness on day 1, which continued at day 7 for the citrate-capped AgNPs only. The 20 nm versus the 110 nm size were more proinflammatory in terms of neutrophil influx, but there was little difference between the citrate-capped versus the PVP-capped AgNPs. AgNPs can induce pulmonary eosinophilic and neutrophilic inflammation with bronchial hyperresponsiveness, features characteristic of asthma.